Integrasi Nilai Tri Hita Karana dalam Pelestarian Tradisi 'Belanjakan' sebagai Identitas Budaya Lokal di Kecamatan Masbagik Kabupaten Lombok Timur - Jamaludin; Rusdiana Yusuf; Adi Suriatno (Journal of Mandalika Literature, 2025)
The preservation of local culture is a crucial element in maintaining a community's identity, reflecting its values, history, and wisdom passed down through generations. This study aims to explore the role of the Tri Hita Karana philosophy in preserving the "Belanjakan" tradition as the local identity of the Sasak community in Masbagik District, East Lombok. Employing a qualitative ethnographic approach, data were gathered through participatory observation, in-depth interviews, and documentation to capture the perspectives of community members, traditional leaders, and participants in the "Belanjakan" tradition. Key findings reveal that Tri Hita Karana-emphasizing harmony between humans and God (Parahyangan), among humans (Pawongan), and with nature (Palemahan)-underpins the "Belanjakan" tradition, thereby strengthening its cultural sustainability. Rituals embody Parahyangan through prayer and purification, Pawongan is represented in community solidarity, while Palemahan is upheld through environmental respect. This cultural practice serves not only as heritage preservation but as character education for the youth. Integrating "Belanjakan" into cultural tourism and education ensures continuity, promoting pride and commitment in upholding Sasak heritage.